Impact of chronic endometritis on assisted reproductive technology outcomes: a propensity score inverse probability weighting cohort study - Huang, Wenjie; Duan, Liqiong; Wei, Liuyan; Tang, Ni; Wei, Jia; Chou, Xuechang; Ma, Yaping; Wei, Lili; Zhang, Ming; Lu, Fangmei; Fan, Li; Wang, Kai; et al. (Frontiers in Cell and Developmental Biology, 2026)
BackgroundChronic endometritis (CE), characterized by CD138+ plasma cell infiltration, has been proposed to impair reproductive outcomes in assisted reproductive technology (ART). However, current evidence remains inconsistent, and diagnostic criteria vary widely. This study aimed to evaluate whether CE diagnosis and antibiotic treatment influence clinical pregnancy, live birth, and miscarriage outcomes following in vitro fertilization with fresh embryo transfer (IVF-ET) and frozen embryo transfer (FET).MethodsWe retrospectively analyzed 3,041 embryo transfer cycles (1,507 IVF-ET; 1,534 FET) from 1,401 infertile women treated at the Reproductive Medicine Center of Liuzhou Hospital, Guangzhou Women and Children’s Medical Center (2008–2023). Chronic endometritis (CE) was primarily defined as the presence of ≥1 CD138+ plasma cell per 10 high-power fields (HPFs, ×400). Standard therapy was doxycycline 100 mg twice daily for 14 days. Outcomes were analyzed per transfer cycle using Poisson regression with robust standard errors and propensity score weighting.ResultsUntreated CE patients had comparable live birth and clinical pregnancy rates to non-CE patients in both IVF-ET (live birth 37.7% vs. 36.7%) and FET (39.0% vs. 37.9%), and were also associated with a lower observed miscarriage risk after IVF-ET (adjusted RR 0.67, 95% CI 0.46–0.97). Among CE patients, antibiotic treatment did not improve outcomes compared with no treatment (IVF-ET live birth 36.8% vs. 37.7%; FET 41.5% vs. 38.7%; all p > 0.05). Similarly, post-treatment “cured” and “persistent” CE groups showed no significant differences in live birth or miscarriage rates in either transfer type. Exploratory analyses revealed context-dependent trends, but most interactions were nonsignificant.ConclusionIn this large single-center cohort, CE defined by CD138+ plasma cell infiltration was not associated with reduced clinical pregnancy or live birth rates, and no statistically significant benefit of antibiotic treatment was observed. The observed reduction in miscarriage risk among CE patients suggests complex immunological dynamics. Routine CE screening in all ART candidates may be unnecessary, and targeted evaluation for high-risk subgroups warrants further investigation.